2018
DOI: 10.4103/joacp.joacp_346_17
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral nerve blocks for above knee amputation in high-risk patients

Abstract: Background and Aims:Above knee amputation (AKA) is associated with considerable mortality and morbidity. There is paucity of data describing the use of peripheral nerve blocks (PNB) as the sole anesthetic technique in high-risk patients undergoing AKA. Our objectives were to evaluate the use of PNB as sole anesthetic technique in the above-mentioned population and its clinical outcomes.Material and Methods:This was a retrospective descriptive study conducted in a tertiary hospital. For this study, patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Furthermore, complete analgesia/anesthesia are sometimes elusive under PNB despite targeting femoral, lateral femoral cutaneous, obturator (anterior and posterior divisions) and sciatic nerves separately with LA volumes and concentrations approaching the maximum safe threshold – some authors have admitted to exceeding the recommended doses without adverse toxic effects. 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, complete analgesia/anesthesia are sometimes elusive under PNB despite targeting femoral, lateral femoral cutaneous, obturator (anterior and posterior divisions) and sciatic nerves separately with LA volumes and concentrations approaching the maximum safe threshold – some authors have admitted to exceeding the recommended doses without adverse toxic effects. 3 , 4 …”
Section: Discussionmentioning
confidence: 99%
“…Conventional spinal anesthesia has been considered as the gold standard approach for lower limb surgeries but many authors agree that they are best avoided in patients with poor cardiovascular reserve because significant hemodynamic disruption might ensue. 4 , 9 Our ultra-low-dose technique helped us to maintain the MAP and avoid spinal-induced hypotension which is associated with perioperative adverse cardiac events. 10 Using ultra-low-dose neuraxial technique limits the blocked spinal segments, the extent of the sympathetic blockade and minimizes the effect on the systemic vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of the use of this technique is currently unknown. In a retrospective study of 57 high-risk patients, Chandran et al (2018) reported a 91% success rate for patients undergoing above-the-knee amputation under peripheral nerve blocks and sedation [ 5 ]. Not surprisingly, higher levels of sedation were required if only the femoral and sciatic nerves were blocked, rather than also blocking the obturator and lateral femoral cutaneous nerves.…”
mentioning
confidence: 99%